If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(z+5)=5
We move all terms to the left:
(z+5)-(5)=0
We get rid of parentheses
z+5-5=0
We add all the numbers together, and all the variables
z=0
| (3x+5)/(4x+5)=2/3 | | 4+3y/6y-2=-3/5 | | (〖4D〗^4-〖8D〗^3〖-7D〗^2+11D+6)y=0 | | -7=7y+28 | | 4x-6=5(x-7) | | 144/4=n/6 | | (3x+5)/(4x+6)=5/4 | | (2x-1)-5=4x | | x^2+6x+3=-5 | | (6-2x)=-23 | | n^2+6n+3=-5 | | (6-2x)=23 | | 2x/3=4x | | 2.5/5=n/3 | | 5p+16=6 | | (2-3x)-1=0 | | 6(y-2)-3(y+3)-5(y+3)=0 | | 2x+38=3x-26 | | (x-7)+(x+1)=0 | | (-6-5x)=-61 | | (x+3)-(x-2)=4 | | 8+11n=14n–7 | | (x*61)*3.6=43.92 | | x/183=0.24 | | (-6-5x)=61 | | (7x+4)/2x=8 | | (5x)3=30 | | 16=4(z-5) | | 3(t-4)+8=14 | | 3t-4+8=14 | | 6=5u-u^ | | b/8+8=15 |